p53 expression in synovial sarcoma and its association with prognostic factors (Medical Journal of Indonesia, 2012)
Background: Synovial sarcoma is an aggressive tumor and has two common histological subtype, biphasic and monophasic. It has SYT-SSX gene fusion that decreases expression of p53 tumor suppressor. The prognosis is associated with mitosis and tumor diameter. Therefore this study conducted to know the pattern of p53 expresion and its association with mitosis, histological subtype, and other prognosis factors. Methods: Twenty synovial sarcoma cases consisted of 4 monophasic and 16 biphasic cases from Cipto Mangunkusumo Hospital-Faculty of Medicine, Universitas Indonesia (CMHospital-FMUI) 2005-2011 were analyzed for association of p53 expression and mitosis as prognostic factor. Haematoxylin-eosin slides were used to count mitosis. Paraffin block materials were used to analyze p53 expression by immunohistochemistry and to detect SYT gene translocation by FISH (Fluorescein in situ Hybridization). Results: The Fisher's exact test showed that positive p53 expression was associated with tumor diameter <5 cm although it was not associated with mitosis. The histological subtype has no association with p53 expression and mitosis. Unfortunately, only 7/19 cases were positive for FISH-SYT gene translocation. Conclusion: In synovial sarcoma, p53 expression is associated with tumor diameter. (Med J Indones. 2012;21:196-202)